PERAN BUDAYA DAN AGAMA DALAM MENGATASI STUNTING DI JORORNG PAHAMBATAN KENAGARIAN BALINGKA KABUPATEN AGAM - Yuliza Anggraini; Liza Andriani; Villa Wahyu Andari (LPPM Universitas Abdurrab, 2024)
Stunting is a condition where children fail to thrive which results in children being short and the main cause is a lack of nutrition. Several factors that can cause stunting in children include the mother's low knowledge about good nutrition during pregnancy. Therefore, it is necessary to evaluate maternal behavior in efforts to prevent stunting in children, especially in toddlers. The behavior that needs to be evaluated consists of the role of culture, religion, attitudes and actions, by evaluating what the mother has done in efforts to prevent stunting (Fildzah et al., 2020). The research aims to find out in-depth information regarding the role of culture and religion in overcoming stunting in Jorong Pahbatas Kenagarian Balingka. The research method used is qualitative research using the In-depth Interview method. The sampling technique is Purpose Random Sampling, which is adjusted to research considerations and the number of informants deemed sufficient. The number of informants in this research was 4 informants, consisting of guardians, implementing midwives, religious leaders and mothers with toddlers. Research data collection was carried out using interview guidelines. Data processing and analysis is carried out using data transcripts and data reduction including data presentation, conclusions and verification. The results of this research show that the role of culture and religion in overcoming stunting in Jorong Pahbatas is good, but the stunting rate in Nagari is still high so it is necessary to conduct research on mothers, husbands and families using related variables. The conclusion of this research is that in-depth information is known regarding the role of culture and religion in overcoming stunting in Jorong Pahbatas Kenagarian Balingka, Agam Regency.